Supraventricular tachyarrhythmia as a first sign of aortic aneurysm - Antonio Villa; Alfredo Corticelli; Gerarda Russo; Dimitra Zarifi; Andrea Bona; Simona Armieri (Journal of Health and Social Sciences)
We report the case of a 50-year-old man who presented with palpitations, without any other symptoms. An electrocardiogram (ECG) showed rapid supraventricular tachyarrhythmia (atrial flutter 2:1). Transthoracic echocardiography showed severe left ventricular dilatation and left atrial enlargement, sustained by the severe dilatation of the aortic root and an ascending aortic aneurysm. A computed tomography (CT) scan of the chest confirmed the aortic dilatation. Thoracic aortic disease presents in many different ways, often incidentally after a chest X-ray is performed for other reasons. Our patient had no such risk factors for an aortic aneurysm. The existing literature features some reports of aortic dissection presenting with supraventricular arrhythmias, but to our knowledge, this is the first report of an arrhythmia as the first sign of an aortic aneurysm (not dissected). The guidelines for the management of atrial fibrillation do not specify the timing of performing echocardiography. We think that during the assessment of a patient who is in the emergency room with paroxysmal tachyarrhythmias, performing echocardiography early can be very useful.